The MECP2 variant c.925C>T (p.Arg309Trp) causes intellectual disability in both males and females without classic features of Rett syndrome. Issue 6 (8th April 2016) - Schönewolf‐Greulich, B.; Tejada, M.‐I.; Stephens, K.; Hadzsiev, K.; Gauthier, J.; Brøndum‐Nielsen, K.; Pfundt, R.; Ravn, K.; Maortua, H.; Gener, B.; Martínez‐Bouzas, C.; Piton, A.; et al.
Abstract : Abstract : Missense MECP2 variants can have various phenotypic effects ranging from a normal phenotype to typical Rett syndrome (RTT). In females, the phenotype can also be influenced by the X‐inactivation pattern. In this study, we present detailed clinical descriptions of six patients with a rare base‐pair substitution affecting Arg309 at the C‐terminal end of the transcriptional repression domain (TRD). All patients have intellectual disability and present with some RTT features, but they do not fulfill the clinical criteria for typical or atypical RTT. Most of the patients also have mild facial dysmorphism. Intriguingly, the mother of an affected male patient is an asymptomatic carrier of this variant. It is therefore likely that the p.(Arg309Trp) variation does not necessarily lead to male lethality, and it results in a wide range of clinical features in females, probably influenced by different X‐inactivation patterns in target tissues.